2021
DOI: 10.4018/ijesma.2021070101
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Factors Influencing the Intention to Adopt Cloud ERP Systems by SMEs in Jordan

Abstract: This study aims to explore the factors influencing the intention to adopt cloud enterprise resource planning (ERP) systems by small and medium-sized enterprises (SMEs) in Jordan. The research proposes a new model by extending the technology acceptance model (TAM) with four additional factors, including computer self-efficacy, complexity, compatibility, and organizational support. Using a questionnaire, data was collected from 394 subjects. An adaptive neuro fuzzy inference system (ANFIS) was utilized to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…At the individual level, frameworks such as the theory of reasoned action (TRA) [41], technology acceptance model (TAM) [42], the theory of planned behavior (TPB) [43] and UTAUT are well-established for determining individual characteristics in IS adoptions [36]. TAM is a widespread framework to investigate IS adoptions such as cloud ERP [32,44]. The TAM framework examines perceived usefulness and perceived ease of use which are the two main characteristics of technology acceptance and use [45].…”
Section: A Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual level, frameworks such as the theory of reasoned action (TRA) [41], technology acceptance model (TAM) [42], the theory of planned behavior (TPB) [43] and UTAUT are well-established for determining individual characteristics in IS adoptions [36]. TAM is a widespread framework to investigate IS adoptions such as cloud ERP [32,44]. The TAM framework examines perceived usefulness and perceived ease of use which are the two main characteristics of technology acceptance and use [45].…”
Section: A Theoretical Foundationsmentioning
confidence: 99%
“…The use of an integrative model to investigate cloud ERP adoption in SMEs is limited, especially focusing on both the organizational and individual levels [e.g., 30,31,32]. Prior studies have investigated adoption of cloud ERP systems in either an organizational or individual context [25].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on ERP have highlighted the importance of system quality in the actual usage and implementation of ERP systems (Costa et al, 2016;Das & Dayal, 2016). Using the framework of TAM (technology acceptance model), studies have found a significant and positive impact of perceived ease of use on ERP usage intention (Habahbeh & Obidat, 2021;Mayeh et al, 2016). An empirical investigation by Ram et al (2013) has found a significant positive impact of perceived system quality (PSQ) in the successful implementation of ERP projects.…”
Section: System Qualitymentioning
confidence: 99%